Novel Model for The Energy Minimisation of Natural Gas Transmission Networks - Y. Liang; E. Pahija; C.-W. Hui (Chemical Engineering Transactions, 2017)
Natural gas transmission through an extensive pipeline network is an energy consuming process required gas compression due to significant pressure drop. The main difficulties in optimising a natural gas transmission network are the nonconvexities of the pressure drop and the compressor constraints. To address the nonconvex issues, a novel model is proposed and demonstrated using an energy minimisation problem of natural gas transmission networks. The new model overcomes the nonconvexity of the pressure drop constraints by convexifying them into convex constraints, and addresses the nonconvex compressor constraints by rewriting them in to convex constraints and concave constraints. The model is formulated as a mixed-integer nonlinear programming (MINLP) model and tested by two different sizes networks. Computational results show the proposed model significantly reduces the solution time and improve solution quality.